(untitled) (Islamic Sciences Journal, 2023)
The nature of research and investigation required that the researcher presents to the reader something about the author’s life and writings in a preface that preceded the verified text. So the researcher had dealt with the text as is well-known among the investigators, and had explained this in a special paragraph in (The Investigation Method).